Basic and Clinical Aspects of Non-neuronal Acetylcholine: Expression of Non-neuronal Acetylcholine in Lung Cancer Provides a New Target for Cancer - Therapy Pingfang Song; Eliot R. Spindel (Elsevier, 2008)
Lung cancer is the leading cause of cancer death worldwide and new treatment strategies are clearly needed. The recent discovery that lung and other cancers synthesize and secrete acetylcholine (ACh) which acts as an autocrine growth factor suggests that this cholinergic autocrine loop may present new therapeutic targets. In normal bronchial epithelium, small airway epithelium and pulmonary neuroendocrine cells synthesize Ach; and in squamous cell lung carcinoma, adenocarcinoma, and small cell lung carcinoma, the respective lung cancers that derive from those cell types similarly synthesize ACh. ACh secreted by those cancers stimulates growth of the tumors by binding to nicotinic and muscarinic receptors expressed on lung cancers. Thus antagonists to nicotinic and muscarinic receptors can inhibit lung cancer growth. The muscarinic receptor (mAChR) subtype utilized for cell proliferation is the M3subtype and consistent with this M3mAChR antagonists inhibit growth of SCLC and squamous cell carcinomas. This is significant as M3mAChR antagonists have low toxicity and are in wide clinical use. As multiple other cancer types besides lung carcinomas express both M3mAChR and acetylcholine, other cancer types besides lung carcinoma may respond to M3mAChR antagonists. Keywords:: non-neuronal cholinergic system, lung cancer, cancer, non-neuronal acetylcholine, nicotinic receptor, muscarinic receptor